Identification and Sensivity Test of Pseudomonas aeruginosa to Ciprofloxacin and Ceftazidime in Diabetic Ulcers - Safitri Nur Istiqomah; Didik Wahyudi (BIOPENDIX, 2025)
Diabetic ulcers are a serious complication in diabetic patients, often becoming infected with various pathogenic bacteria, including Pseudomonas aeruginosa, which is known for its high resistance to multiple antibiotics. This study aimed to identify the presence of Pseudomonas aeruginosa in diabetic ulcers and evaluate its sensitivity to the antibiotics ciprofloxacin and ceftazidime at the Diabetic Wound Care Center (RUMAT) in Surakarta. The research used a descriptive observational design with the Kirby-Bauer disk diffusion method for antibiotic susceptibility testing, along with bacterial isolation, Gram staining, and biochemical tests for identification. The results showed that out of 8 specimens examined, 4 specimens (50%) were identified as Pseudomonas aeruginosa, all of which demonstrated sensitivity to ciprofloxacin and ceftazidime, with inhibition zones above the sensitive standard according to CLSI M100 2023.